Determinants of Industry 4.0 Readiness in the Manufacturing of the V4 Economies - Edward Molendowski; Kinga Nawracaj‑Grygiel; Marta Ulbrych (Comparative Economic Research)
The article presents the results of research aimed at identifying the determinants of Industry 4.0 (I4.0) readiness in manufacturing and assessing the relevant progress made by the Visegrad Group (V4; i.e. the Czech Republic, Hungary, Poland and Slovakia) countries between 2011 and 2021. The investigation relies on the authors’ proposal for twelve variables that constitute the basis for a study using principal component analysis (PCA). Based on the calculation of factor loadings, the study produces a composite indicator of I4.0 readiness. It is followed by an assessment of the V4 economies against the backdrop of the other EU Member States. The V4 economies showed relatively low levels of I4.0 readiness and made no significant progress. The top performer was the Czech Republic, ranked 12th, on average, between 2011 and 2021. It was closely followed by Hungary (14th) and Slovakia (17th). Poland was ranked the lowest (20th). The main contribution is the proposal of a set of determinants of I4.0 readiness in manufacturing. Measuring the progress of I4.0 readiness in the V4 economies and identifying barriers to I4.0 implementation in manufacturing may have application value for public policies.